MODIFIKASI FOTOBIOREAKTOR HEMAT ENERGI DENGAN LIGHT EMITTING DIODE (LED) UNTUK MENINGKATKAN POPULASI Chlorella spp. DALAM UPAYA PEMENUHAN PAKAN ALAMI LARVA IKAN BANDENG - Rosady, Siti Duratun Nasiqiati; Kusumadewayanti, Esthi; Amanatin, Dwi Riesya; Nasikhin, Roksun; Fiqar, Tegar Palyus (UPN VETERAN JAWA TIMUR, 2012)
Fotobioreaktor experiments with fluorescent light sources have been reported can increase the efficiency of photosynthesis in fitoplankton. The results of such experiments show that the density of the fitoplankton culture in fotobioreaktor in line with increasing the intensity of light . Chlorella vulgaris grown in fotobioreaktor with sea water and walne medium. The trial was done with treatment intensity variations of different light sources, namely light source LED 1 X 3 watt LED 2 X 3 Watts. Fotobioreaktor placed in a box by a distance of 10 cm from a source of light. Fotobioreaktor used as a comparison with Neon light source 1 X 8 Watts and Neon 2 X 8 watts. Two-factor ANOVA analysis showed that (p> 0,05), it means there are no interaction effect a between the sides and the source of light . Fotobioreaktor led light source with 1 x 3 watts capable of producing Chlorella vulgaris density equal to fotobioreaktor source of a fluorescent with 2 x 8 watts. The result indicates fotobioreaktor light source with power 3 watt more efficient in the use of electrical energy to produce a density of Chlorella vulgaris. This provides an indication that fotobioreaktor with energy-efficient LED light source and are able to increase the density of Chlorella Vulgaris.Keyword: Chlorella Vulgaris, Led Emitting Diode, Economical Energ